Deciphering the demographic history of allochronic differentiation in the pine processionary moth Thaumetopoea pityocampa. Issue 1 (29th November 2017) - Leblois, R.; Gautier, M.; Rohfritsch, A.; Foucaud, J.; Burban, C.; Galan, M.; Loiseau, A.; Sauné, L.; Branco, M.; Gharbi, K.; Vitalis, R.; Kerdelhué, C.
Abstract: Understanding the processes of adaptive divergence, which may ultimately lead to speciation, is a major question in evolutionary biology. Allochronic differentiation refers to a particular situation where gene flow is primarily impeded by temporal isolation between early and late reproducers. This process has been suggested to occur in a large array of organisms, even though it is still overlooked in the literature. We here focused on a well‐documented case of incipient allochronic speciation in the winter pine processionary moth Thaumetopoea pityocampa . This species typically reproduces in summer and larval development occurs throughout autumn and winter. A unique, phenologically shifted population (SP) was discovered in 1997 in Portugal. It was proved to be strongly differentiated from the sympatric "winter population" (WP), but its evolutionary history could only now be explored. We took advantage of the recent assembly of a draft genome and of the development of pan‐genomic RAD‐seq markers to decipher the demographic history of the differentiating populations and develop genome scans of adaptive differentiation. We showed that the SP diverged relatively recently, that is, few hundred years ago, and went through two successive bottlenecks followed by population size expansions, while the sympatric WP is currently experiencing a population decline. We identified outlier SNPs that were mapped onto the genome, but none were associated with the phenological shift or with subsequent adaptations. The strong genetic drift that occurred along the SP lineage certainly challenged our capacity to reveal functionally important loci.